PERTUMBUHAN PDRB TANAMAN BAHAN MAKANAN DAN KONTRIBUSINYA TERHADAP PEREKONOMIAN PROVINSI RIAU - Rini Nizar; Anto Ariyanto (Universitas Lancang Kuning, 2016)
The slow growth in harvested area and production of food crops ( rice, corn and soybeans ) have an impact on the occurrence of lack of food supply , especially rice . This deficiency is imported from outside the region which will also affect the economy's income Riau province mainly of income from the agricultural sector . This article examines the growth of food crops and its contribution to the economy in the province of Riau The analytical method used is descriptive and quantitative approach to literature reviews, and search was secondary data .The results show that the GDP growth and the contribution of the food crops sub-sector is still small relative to the economy of the province of Riau . to maintain the availability of foodstuffs , especially rice governments should make efforts to increase the area of land and increased productivity